Beban kerja karyawan perbankan, implikasinya terhadap kinerja karyawan melalui variabel motivasi - Ulfatun Ni'mah; Siswanto Siswanto (STIE Perbanas Surabaya, 2016)
Employee performance is an important work attitude for achieving or-ganizational goals. In this case, motivation and workload variable can increase performance of employee. This paper aims to determine the effect of workload on employee performance directly. In addition, this study aims to investigate the effect of workload on employee performance indirectly through motivation variable. This research relies on path analysis. The research sample consists of 74 people. The results show that workload has increased directly employee performance. In addition, the workload has affected employee performance through motivation variable as well. The impact of workload variable to employee performance has greater influence indirectly through motivation variable. Giving the employees tasks according to their ability have increased effectively employee motivation.